Comparative Degradome Analysis of the Bovine Piroplasmid Pathogens Babesia bovis and Theileria annulata - Poklepovich Caride, Tomás Javier (2023)
Babesia bovis and Theileria annulata are tick-borne hemoprotozoans that impact bovine health and are responsible for considerable fatalities in tropical and subtropical regions around the world. Both pathogens infect the same vertebrate host, are closely related, and contain similar-sized genomes; however, they differ in invertebrate host specificity, absence vs. presence of a schizont stage, erythrocyte invasion mechanism, and transovarial vs. transstadial transmission. Phylogenetic analysis and bidirectional best hit (BBH) identified a similar number of aspartic, metallo, and threonine proteinases and nonproteinase homologs. In contrast, a considerably increased number of S54 serine rhomboid proteinases and S9 nonproteinase homologs were identified in B. bovis, whereas C1A cysteine proteinases and A1 aspartic nonproteinase homologs were found to be expanded in T. annulata. Furthermore, a single proteinase of families S8 (subtilisin-like protein) and C12 (ubiquitin carboxyl-terminal hydrolase), as well as four nonproteinase homologs, one with dual domains M23-M23 and three with S9-S9, were exclusively present in B. bovis. Finally, a pronounced difference in species-specific ancillary domains was observed between both species. We hypothesize that the observed degradome differences represent functional correlates of the dissimilar life history features of B. bovis and T. annulata. The presented improved classification of piroplasmid proteinases will facilitate an informed choice for future in-depth functional studies.